Epidemiologi dan Dampak Ekonomi Wabah African Swine Fever di Provinsi Nusa Tenggara Timur - Wera, Ewaldus; Bulu, Petrus Malo; Tukan, Const Joel Misery; Medah, Jacob Nehemia; Dhaja, Claudya Anastasia; Sagala, Endah Budiati; Purwengtyas, Setijanti; Irawan, Bayu; Christopher, David Alvin; Winata, Renardi; Angsar, Melky; Tabali, Zulkifli; Marjaya, Siviardus (JURNAL KAJIAN VETERINER, 2025)
This study evaluated the epidemiology and economic impact of African Swine Fever (ASF) at the household farmer (HF) level in East Nusa Tenggara (NTT) Province, Indonesia. The economic and epidemiological data were obtained from interview with 97 farmers across seven districts. The prevalence of ASF at farmer level was calculated based on the number of HF experienced ASF outbreak in certain year divided by total HF interviewed. The total economic losses due to ASF outbreak were calculated based on the economic value of pig, cleaning and disinfection of stalls, stall depreciation, leftover feed, and reduced value of pigs. Approximately 90% of the respondents reported pig mortalities associated with ASF during the initial outbreaks in 2020-2021. The total economic losses due to ASF outbreak were estimated to be IDR 1,4 billion, averaging IDR 14,5 (percentile 5th;95th: 5,1;27,8) million per household farmer per year, with losses dominated by pig mortality (92%). Losses varied by districts, with the highest in East Sumba (17,9 million per HF) and the lowest in Rote Ndao (11,5 million per HF). These findings demonstrate that ASF outbreak is financially loss for smallholder pig farmers and can significantly reduced their income. Optimizing biosecurity implementation at household farm level could be financially beneficial for smallholder pig farmers and can significantly mitigate ASF-related economic losses in NTT.